Redistribution process of precipitation in ecological restoration activity of Pinus sylvestris var. mongolica in Mu Us Sandy Land, China - Yiben Cheng; Hongbin Zhan; Wenbin Yang; Wei Feng; Qi Lu; Yunqi Wang; Qunou Jiang; Bin Wang; Mingchang Shi; Tao Wang; Zhiming Xin; Ruifang Hao (International Soil and Water Conservation Research, 2023)
Precipitation is the most important water resource in semi-arid regions of China. The redistribution of precipitation among atmospheric water, soil water and groundwater are related to the land surface afforested ecological system. The study took widely replanted Pinus sylvestris var. Mongolica (PSM) in Mu Us Sandy Land (MUSL) as a research object and monitored precipitation, soil moisture, sap flow, and deep soil recharge (DSR) to find out moisture distribution in shallow soil layers. Results showed that the restoration process of PSM in MUSL changed the distribution of precipitation, with part of it infiltrating downward as DSR and part of it being stored in the shallow soil. Consequently, evapotranspiration increased and DSR significantly decreased, resulting in up to 466.9 mm of precipitation returning to the atmosphere through evapotranspiration in 2016. Vegetation increased soil water storage (SWS) capacity, with maximum SWS in PSM plot and bare sandy land (BSL) being 260 mm and 197 mm per unit horizontal area, respectively in 2016. DSR decreased from 54% of precipitation in the BSL plot to 0.2% of precipitation in the PSM plot in 2016. A great portion of infiltrated water was stored in the PSM ecosystem, resulting in a time lag of infiltration to reach the deep soil layer, and the infiltration rate in the BSL plot was 11 times of that in the PSM plot. SWS decreased 16 mm and 7.6 mm per unit horizontal area over a one-year period (from March to October, non-freezing time) in 2017 and 2019, respectively. The PSM annual sap flow was maintained at a relatively constant level of 154 mm/yr. Through in-situ measurement and comparative analysis of the precipitation redistribution of the BSL plot and the PSM plot, we find that PSM can significantly reduce the shallow soil water storage and DSR. However, substantial reduction of shallow soil water storage and DSR is detrimental for the long-term development of PSM forest. Therefore, it is necessary to reduce PSM density to cut the water consumption by PSM per unit area, thus to augment the shallow SWS and DSR, which will be beneficial for the PSM to survive under extreme drought conditions in the future. This study helps us understand the role of precipitation-induced groundwater recharge in the process of vegetation restoration in semi-arid regions and explains the possible causes of PSM forest degradation.